Blood pressure and lipid profile in young women: the role of anthropometric measurement - Rubira, Marcelo Custódio; Rubira, Ana Paula Fernandes de Angelis; Rubira, Lucas de Angelis; Lima, Milton Carlos Martins; Franco, Roberto Jorge da Silva [UNESP]; Consolim-colombo, Fernanda Marciano (Escola de Educação Física e Esporte da Universidade de São Paulo, 2014)
Body composition has fundamental importance in the quality of life and is a powerful predictor of mortality and morbidity in humans. The identification and monitoring of the amount of body fat have been receiving special attention in aspects related to health promotion, not just for its actions in the prevention and in the control of cardiovascular diseases but also for their induction and association with risk factors, especially in the plasmatic lipid levels and arterial pressure. It was investigated the relationship between body mass index (BMI) and body fat percentage (%BF) by bioelectrical impedance analysis (BIA) with the blood pressure levels (systolic and diastolic) and serum lipids (TC, HDL-c, LDL-c, VLDL-c, TG). In a group of fifty seven women (aged 18 to 26 years old ), obesity was detected in 5 and 19 women by BMI (≥ 30 kg/m2) and %BF (≥ 30%), respectively. BMI and % BF were positively correlated with blood pressure (systolic and diastolic), and highly significant in the obese group by %BF. Moreover, BMI and % BF were significantly correlated with all lipids and lipoprotein fractions VLDL-c and triglyceride, respectively. These results suggest that %BF is a good indicator of “occult obesity” in subjects with normal body mass index. The associated use of BMI and %BF to better evaluate obesity may improve the study of blood pressure levels and serum lipid changes that are commonly associated with obesity.

Composição corporal tem importância fundamental para a qualidade de vida e é um forte preditor de mortalidade e morbidade nos seres humanos. A identificação e o monitoramento da quantidade de gordura corporal têm recebido atenção especial no que se refere aos aspectos relacionados com a promoção da saúde, não apenas de suas ações na prevenção e no controle das doenças cardiovasculares, mas também pela sua associação com fatores de risco, especialmente em níveis de lipídeos plasmáticos e da pressão arterial. Foi investigado a relação entre o índice de massa corporal (IMC) e percentual de gordura corporal (% GC) pela bioimpedância elétrica (BIA), com os níveis de pressão arterial (sistólica e diastólica) e lipídeos séricos (CT, HDL-c, LDL-c, VLDL-c, TG). Em um grupo de 57 mulheres (com idades entre 18 e 26 anos de idade), a obesidade foi detectada em cinco e 19 mulheres, IMC (≥ 30 kg/m2) e % BF (≥ 30%), respectivamente. IMC e % GC foram positivamente correlacionados com a pressão arterial (sistólica e diastólica), e altamente significativos no grupo dos obesos pelo % GC. Além disso, o IMC e % GC foram significativamente correlacionados com todos os lipídios e frações de lipoproteínas VLDL-C e triglicérides, respectivamente. Estes resultados sugerem que o % GC é um bom indicador de “obesidade oculta” em indivíduos com índice de massa corporal normal. Que o uso associado de IMC e % GC para melhor avaliar a obesidade pode melhorar o estudo dos níveis de pressão arterial e alterações de lipídios que é geralmente associada à obesidade.
Pressão arterial e perfil lipídico em mulheres jovens: o papel da avaliação antropométrica
Keywords: Índice de massa corporal; Bioimpedância elétrica; Obesidade; Pressão arterial; Lipídios; Body mass index; Bioelectrical impedance; Obesity; Blood pressure; Lipid